Pertumbuhan ekonomi dan ketimpangan pembangunan ekonomi antar wilayah kebijakan pembangunan di Provinsi Jawa Timur - Maretha Berlianantiya (Universitas PGRI Madiun, 2017)
This study aimed toknow the relationship and the pattern between economic growth and inequality of economic development in East Java at 2004- 2013. It is determined by the characteristics of development policy area in East Java at 2004- 2013.This research is carried out in East Java province that contains of 29 regencies and 9 cities. They are divided into 4 Bakorwil. This research uses the secondary data, then analyzed by analysis technique of Williamson Index to measure development inequality, correlation of moment product and Regression Curve Estimation.The results of this research are (1) the relationship pattern between economic growth and development inequality tends to be “U” so Kuznets hypothesis does not apply in East Java, and the correlation value of product moment does not significant so the relationship economic growth and development inequality cannot be described. (2) In each Bakorwil, the relationship pattern between economic growth and inequality of economic development is influenced by the characteristics of development policy area in East Java province, likewise with its correlation.